Structure Optimization Analysis of Two Tooth Difference External Mesh Duplex Planetary Gear Transmission - Liu Chang; Zhou Zhebo; Ye Youdong; Zhao Qigang; Li Xiaoqin (Jixie chuandong)
Based on analyzing and researching on the structural features and failure mode of a two teeth difference outer mesh planetary gear transmission,according to the existing traditional structure form,a new method to optimize the structure and parameters of the two- tooth difference external meshing duplex planetary gear transmission is proposed,it is basically meet the requirements of equal sliding coefficient,the meshing performance and life between meshing gears could be improved effectively.